Impact of duration of kangaroo mother care on growth in preterm and low birth weight neonates: a prospective cohort study - Surandran, Sukrutha; Nagendra K. (International Journal of Contemporary Pediatrics, 2023)
Background: Care of low-birth-weight infants is one of the most important challenges faced globally. Kangaroo mother care (KMC) is a simple and powerful, yet most cost-effective means to provide warmth, nutrition, protection from infections, caring environment and bonding, thus promoting growth. Aim was to study the impact of duration of KMC on growth in preterm low birth weight (LBW) infants. Methods: This prospective cohort study was done in the NICU and postnatal ward in a teaching institute in Karnataka. All preterm neonates weighing 1500-2000 gm with stable hemodynamics were included in this study and allotted into two groups based on average duration of KMC per day-group I (KMC 4 hours), and group II (KMC 8 hours). All these neonates were monitored daily during their stay in the hospital and advised follow up till 6 weeks of life. The impact of KMC on growth was measured in terms of anthropometric parameters every two weeks, till 6 weeks of post-natal life. Results: With increase in duration of KMC there was significant improvement in the anthropometric parameters (p=0.001). Those infants in group I had mean weight gain of 10.5 gm/day, length 0.80 cm/week, head circumference 0.62 cm/week, and chest circumference 0.73 cm/week. Those in group II had a mean weight gain of 15.07 gm/day, length 0.85 cm/week, head circumference 0.71 cm/week and chest circumference of 0.81 cm/week. Conclusions: There were significant increments in anthropometric parameters when the duration of KMC per day increased. KMC can be implemented in all the healthcare centres especially in resource poor settings.